Analisis Batasan Usia Sebagai Syarat Kecakapan Untuk Menghadap Ke Notaris - Videmarsha Anasuciara Prabaswara (CV. ITTC INDONESIA, 2025)
Legal pluralism in Indonesia regulates various age limits in relation to the capacity to perform legal acts, including appearing before a Notary. Several laws and regulations such as the Civil Code, Marriage Law, Notary Office Law, and other laws and regulations provide different age limits. The problem arises when faced with a condition where a person must perform legal acts before a Notary, which legislation is used to determine the age limit for that person. Thus, this research aims to find out the exact age limit for parties who want to perform legal acts before a Notary. This research is a normative legal research that uses 2 (two) approach methods, namely the statue approach and conceptual approach. This research produces answers to legal issues that arise that the age limit to appear before a notary is guided by the Notary Position Law as Lex Specialis, which is at least 18 (eighteen) years old or married.